Risk and Foreign Direct Investment - White, C. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2006)
Incorporating an accurate measure of risk is important to the appraisal of an international investment. This book examines and recommends how decisions on international investment projects are made. Critiquing and integrating existing theory, it shows how risk can be incorporated into the present value formula produce a clear decision rule.